Advanced fluidized bed-ultrafiltration-reverse osmosis process for near-complete fluorine recovery from photovoltaic fluoride-laden wastewater: system parameters and mechanisms - Wang, Ao; Xie, Hangang; Xu, Hang; Huang, Wenwen; Ma, Jun; Hu, Tianlong; Wang, Jingjun; Lin, Tao; Ding, Mingmei (Water research (Oxford), 2025)
•An integrated FBUR process enables resource recovery from fluoride-laden wastewater;•High-purity fluorite is recovered during the FBUR process;•Crystallization and fouling mechanisms are revealed by cluster theory and force field analysis;•FBUR is competitive according to life cycle assessment. Industrial fluoride-laden wastewater has emerged as a critical environmental challenge due to the rapid growth of photovoltaics and battery industries. This study proposes a novel, integrated and expandable fluidized bed-ultrafiltration-reverse osmosis (FBUR) process. The fluidized bed component targets F− crystallization, while ultrafiltration (UF) and reverse osmosis (RO) membrane units concentrates fluidized bed effluent. The concentrated brine was recirculated into the fluidized bed to enhance crystallization efficiency, enabling simultaneous water purification and fluorite recovery from photovoltaic wastewater. The effects of Ca2+ dosage, upflow velocity, seed crystal, temperature, pH and water recovery rate on the system were investigated, ultimately achieving 99.7 % F− recovery. The optimized process reclaimed water and recovered fluorite of exceptional quality, ensuring that both met high standards. Membrane fouling on UF and RO membranes was characterized using scanning electron microscopy, atomic force microscopy, and optical coherence tomography. Furthermore, the free energy and energy barriers associated with cluster crystallization were calculated based on cluster nucleation theory, and the fouling formation process on the UF membrane surface was analyzed through theoretical computations of the van der Waals-friction-hydrodynamic force field. The results demonstrated that, in the FBUR process, small CaF2 particles exhibited a tendency to detach from the membrane surface, whereas adhered particles could grow further, ultimately leading to the formation of a loose cake layer. These results emphasize the critical importance of determining optimal concentration effluent levels during transitions between sequential units. This study provides an efficient solution for recovering valuable resources from industrial wastewater, thereby advancing sustainable wastewater management. [Display omitted]